Tingkat Kerusakan Lahan Akibat Penambangan Mineral Non-Logam dan Batuan di Daerah Semin, Kabupaten Gunungkidul, Daerah Istimewa Yogyakarta dengan Metode Analytical Hierarchy Process (AHP) - Doni Ardiansyah; Wawan Budianta (PROMINE, 2018)
Mining activities often cause land damage. Land damage can be monitored from time to time, so it canbe controlled and solved. This research was conducted in Semin, Gunungkidul Regency, SpecialRegion of Yogyakarta, from November 2017 until March 2018. Semin area consist of many miningactivities and also directly adjacent with Central Java Province in the east and north. Therefore, thestudy of land damage caused by mining activities in this area is very important. The purpose of thisresearch is to know and study the condition of land damage caused by current mining activities. Themethod used in this research is weighting method by using Analytical Hierarchy Process (AHP) tosome parameters which mostly refers to the Decision of Governor of DIY Number 63 year 2003 asobserved parameter, that is 1) The character of rock compilation of excavation, 2) rock fracturing level3) Utilization and management of top soil, 4) Depth of excavation / height of wall, 5) Limit of slope ofexcavation, 6) Reclamation time, 7) Amount of erosion, 8) River flow / sedimentation. The level ofdamage is divided into three, based on the value, that is 1) Good (1.00-1.66), 2) Medium (1.67 - 2.33),and 3) Damaged (2.34 - 3.00). Total mine sites observed were 81 mine sites. There are 10 mine sitesincluded in the Good category, 68 mine sites belonging to the Medium category, and 3 mine sites inthe Damaged category.